2021
DOI: 10.14710/nmjn.v11i3.36783
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Depression among Indonesians during the COVID-19 Outbreak

Abstract: Background: The 2019 Coronavirus pneumonia disease (COVID-19) has gained intense attention globally, including in Indonesia. The rapid transmission and clinical effects of the virus can cause depression in Indonesian society. However, information on risk factors for depression during COVID-19 in this country is not known. Purpose: This study aimed to determine the level of depression and identify factors influencing depression in Indonesian society during the COVID-19 outbreak.Methods: An online-based cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
1
1
0
1
Order By: Relevance
“…The finding related to COVID-19 patients is also accords with that of Sarfika et al (2021) involved 1,622 participants from 34 provinces in Indonesia and reported that the prevalence of depression in Indonesia was 28.5% mild depression, 18.4% moderate depression, and 24.8% severe depression. In addition, social media exposure (SME), age, gender, occupation, and selfrated health (SRH) was significantly influencing depression (p<0.05) (Sarfika et al, 2021).…”
Section: Theme 1 Experience At Diagnoses (Pre-isolation)supporting
confidence: 85%
“…The finding related to COVID-19 patients is also accords with that of Sarfika et al (2021) involved 1,622 participants from 34 provinces in Indonesia and reported that the prevalence of depression in Indonesia was 28.5% mild depression, 18.4% moderate depression, and 24.8% severe depression. In addition, social media exposure (SME), age, gender, occupation, and selfrated health (SRH) was significantly influencing depression (p<0.05) (Sarfika et al, 2021).…”
Section: Theme 1 Experience At Diagnoses (Pre-isolation)supporting
confidence: 85%
“…Besides smartphones, several factors such as parenting styles, family conflicts, and social or environmental changes [26]- [30], can also impact adolescent mental health. Smartphones affect not only psychosocial, affective, and behavior but also physical well-being, causing eye and finger disorders and neck pain [10], [21].…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini dapat menjadi stresor yang berdampak pada kesehatan mental penderita. Penelitian terkait juga mengemukakan bahwa individu yang menilai kesehatannya buruk, berpotensi 2,72 kali lebih cenderung untuk merasa lebih tertekan selama pandemik COVID-19 (Sarfika et al, 2021). Deteksi dini atau skrining kesehatan dapat dijadikan upaya preventif untuk melacak masyarakat yang beresiko atau pun yang telah mengalami gejala namun tidak tahu bahwa telah terjangkit penyakit (Nofita et al, 2022;Sarfika et al, 2023)…”
Section: Hasil Dan Pembahasanunclassified